Pseudo-Subarachnoid Hemorrhage: A Potential Imaging Pitfall Associated with Diffuse Cerebral Edema - Given, Curtis A.; Burdette, Jonathan H.; Elster, Allen D.; Williams, Daniel W. (American Journal of Neuroradiology, 2003)
Summary: We report CT findings in seven patients with diffuse cerebral edema and increased attenuation in the basilar cisterns resembling subarachnoid hemorrhage. On the basis of autopsy (three cases) and lumbar puncture (four cases) findings, true subarachnoid hemorrhage was reasonably excluded. Pathophysiologic changes that occur with diffuse cerebral edema are explored, with proposed explanations for the appearance of a pseudo-subarachnoid hemorrhage.